Modern Retellings of Beowulf - Slabihoudek, Filip (Univerzita Pardubice, 2025)
This thesis analyzes retold versions of Beowulf and compares them to the original Old English poem. The theoretical part offers an insight into the concept of retellings and issues related to transferring the original version into another medium. The practical part focuses on the characters of Beowulf and the influences that impacted them in the retold versions.
Moderní převyprávění Beowulfa
Keywords: převyprávění; Beowulf; postavy; postmodernismus; filmy; retellings; Beowulf; characters; postmodernism; film